Nutritional risk stratification management is associated with reduced disease relapse and improved quality of life in IBD patients: a retrospective study - Li, Xia; Ma, Shuli; Zhang, Xuxin; He, Hongmei (Frontiers in Nutrition, 2026)
ObjectivesTo investigate the effects of nutritional risk stratification management on relapse control and quality of life (QoL) in patients with Inflammatory Bowel Disease (IBD), and to evaluate the clinical value of systematic nutritional intervention in the comprehensive management of IBD.MethodsThis single-center retrospective cohort study analyzed 752 IBD patients (408 with ulcerative colitis and 344 with Crohn’s disease) who were managed in the Department of Gastroenterology at the Affiliated Hospital of Nantong University between January 2024 and December 2024. Patients were classified into an intervention group if they were managed under an institutional nutritional risk stratification pathway, which included dietitian-led screening with NRS-2002 or MUST and individualized nutrition plans with scheduled reassessment. Patients who received conventional care without entering this structured pathway served as the comparison group. All data, including nutritional status, inflammatory markers, disease activity, relapse events, hospitalization outcomes, and quality of life (IBDQ), were obtained retrospectively from electronic medical records and follow-up databases. Time-to-relapse was analyzed with Cox regression, and changes in continuous outcomes were evaluated using linear mixed-effects models. Propensity score matching and inverse probability of treatment weighting were used to mitigate measured confounding.ResultsIn this observational analysis, significant improvements from baseline were observed in the intervention group for body weight, BMI, and laboratory nutritional indicators (all p < 0.001). Increases in albumin and prealbumin showed a significant negative correlation with the decrease in inflammatory markers (r = −0.42, p < 0.001). The median CRP level decreased from 15.2 to 9.6 mg/L (p < 0.001), and fecal calprotectin decreased from 298 to 184 μg/g (p < 0.001). Disease activity scores (HBI and Mayo) significantly decreased in both CD and UC patients (all p < 0.001). After a median follow-up of 9.8 months, the relapse rate was significantly lower in the intervention group (20.5%) compared to the control group (34.8%) (p < 0.001). Cox regression analysis indicated that nutritional management was independently associated with a reduced risk of relapse (adjusted HR = 0.61, 95% CI: 0.46–0.83, p = 0.001). Furthermore, the intervention group had significantly lower hospitalization rates (12.7% vs. 20.9%, p = 0.009) and shorter hospital stays (6 days vs. 8 days, p = 0.015). Regarding QoL, the total IBDQ score increased significantly in the intervention group (Δ = +13.5, p < 0.001), and the significant time × group interaction (p < 0.001) suggested sustained, cumulative improvement. Subgroup and sensitivity analyses yielded consistent results, supporting the robustness of this association (IPTW HR = 0.59, 95% CI: 0.44–0.81, p = 0.001).ConclusionIn this single-center retrospective cohort, exposure to nutritional risk stratification management was associated with better nutritional status, lower inflammatory markers and disease activity, reduced relapse and hospitalization rates, and improved quality of life in IBD patients. These findings support the hypothesis that integrating structured nutritional risk screening and individualized nutrition management into routine IBD care may be beneficial. However, given the observational design and potential residual confounding, the observed associations should not be interpreted as definitive causal effects, and prospective multicenter randomized studies are needed to confirm these results and guide clinical practice.